The motor vehicle - Garrett, T. K.
"As a reference book it has to be classed as one of the best! There should be a copy of it in every college library."Association of Motor Vehicle Teachers' NewsletterThe Motor Vehicle has been an essential reference work for both the student and practising engineer ever since the first edition appeared in 1929. Today it is as indispensable to anyone with a serious interest in vehicle design techniques, systems and construction as it was then. The current edition has undergone a major revision to include seven new chapters. These include Electric Propulsion; covering all aspects from lead ac